Sosialisasi Pemilu 2024 kepada Pemilih Pemula di Sekolah Pelita Utama Batam - Aparianto Aparianto; Christina Christina; Vincent Lim; Clara Aurelia; Zoey Julyance; Amelia Amelia; Paerin Paerin; Lionel Derrick; Livvy Rinoa; Jesslyn Jesslyn; Selvi Selvi; Felicia Diana Rose; Andy Andy; Sri Indah Lestari; Enrico Sanjaya; Viona Agustin; Joycelyn Joycelyn; Jonsfir Daus Aritonang (National Conference for Community Service Project (NaCosPro), 2023)
Elections in Indonesia are one of the concrete manifestations of Indonesia's democratic ideology, in which the people declare their sovereignty over the state and government. That way, people's participation in this election is quite significant as an indicator of the democratic process in Indonesia. Every year, new voters on the electoral voter list will increase. Those are what that is called as a first-time voter. Beginner voters are the ones who are voting or contributing to election activities for the first time. Therefore, it is necessary to find a way to provide insight and make them aware of the importance of their role in state activities. There's a way or method that can be done by carrying out political socialization with the theme of elections. With socialization, of course, it will have a significant effect or impact on these first-time voters.